ALGUNAS PRECISIONES DE LOS HUMANISTAS A LA SATIRA V DE PERSIO - Fortuny Previ, Filomena (Myrtia, 1997)
The nature and difficulty of Persius' work has demanded a wider explanation of the text. This fact has provoked that these difficulties not only been solved but also have been enlarged. In this essay the glosses made by the humanists about controversial points in the Satyre V lines 19-20, 24-25 and 73-75 are analysed, coming to the conclusion that their comments are still in full force and worth considering.